Avaliação da adição de nanopartículas de sílica nas propriedades mecânicas de polímeros odontológicos - Mussatto, Cristiane Maria Boniatti (2021)
The aim of this study was to increase the knowledge about the effect of the addition of nanoparticles on the mechanical properties of resins. In the first article, was to evaluate in vitro the effect of the incorporation of silanized and non-silanized silica nanoparticles (~160 nm) in mechanical properties and surface roughness of self-cured acrylic resins. Five groups of samples were produced (n=6), following the ISO 20795-1:2013 specifications. In the control group (Ctrl), no particles were added in the resin composition. Non-silanized silica nanoparticles were added either into the polymer (0.7 wt%, group G1) or into the monomer; (0.27 wt%, G2). Two similar groups were formed for composite resins with silanized nanoparticles (groups G3 with 0.7 wt% incorporated into the polymer, and G4 with 0.27 wt% added into the monomer). Data were submitted to Shapiro-Wilk (α=0.05) and ANOVA/Tukey (α=0.05). No significant differences were recorded for the Vickers microhardness among the different groups. Nanoparticle loaded resins, however, showed a 20-30% reduction in flexural strength, depending on the group. Surface silanization, caused no significant effect on improvement in the mechanical behavior of the nanoresins, but appears to improve dispersibility, as indicated by a smaller surface roughness. In the second article, an in vitro study, the self-curing resin and printing resin with DLP technology (digital light processing) with the addition of silica nanoparticles (~ 63 nm) was investigated and compared with PMMA blocks and thermopolymerizable resin for flexural strength and roughness. Eight groups were created (n = 12): self-curing resins, printing resin, PMMA block for milling and thermopolymerizable resin. They differ in nanofiller content and manufacturing techniques. The groups G1, G2, G3 and G4 were made with self-cured resin. The group G1 is control (resin without the addition of nanoparticles). In the group G2 0.5 wt%, G3 1.0 wt%, G4 1.5 wt% of s-SiO2-NP were added to the liquid monomer. The group G5 is print resin whithout nanoparticles. In the group G6 was added 1.0 wt% of s-SiO2-NP into printing resin with DLP technology (digital light processing). The G7 group is a circular PMMA block for milling. The group G8 is thermopolymerizable resin. For each group, measurements of the flexural strength and surface roughness, were performed, as described below. Data were firstly submitted to Kolmogorov-Smirnov normality test, and then evaluated by oneway ANOVA, followed by post-hoc Tukey test, when significant differences between groups were found. The significance level was considered p <0.05. One-way ANOVA showed statistically significant differences among the tested groups for flexural strength (F=79.81, p < 0.05) and surface roughness (F=48.75, p< 0.05). The Tukey HSD post hoc test determined higher flexural strength values in the milled (CAD-CAM) material (G7) (105.86 MPa) and the lower value in the printing resin G5 (35.46 MPa) and printing resin 1 wt% G6 (35.08 MPa) statistical difference (p <0.001). The milling block (CAD-CAM) also showed statistical difference when compared with the self-cured resin groups (G1, G2, G3 and G4) and themopolymerizable resin group (G8). The Tukey HSD post hoc test determined higher surface roughness values (0.67μm) in the group G7 (milling block CAD-CAM) and the lower value (0.21 μm) in the group G8 statistical difference (p<0.000). The thermopolymerizable group (G8) showed no significant difference between sellf-cured resins groups (G1, G2, G3 and G4). The second highest surface roughness value was for the printing resin groups (G5, G6) statistical difference from all groups, but no significant difference each other. Clinically, the improvement in the flexural strength has positive effects, such as greater durability of extensive temporary bridgeworks which must remain functional for long periods of time, specially in patients with para-functional habits. Such qualities are present in the samples manufactured with PMMA blocks (G7). Based on the findings of this study, the printed resin (G5 and G6) for manufacturing high-durability temporary parts or articulated plaques is not recommended, since the flexural strength remained considerably under the level recommended by the ISO(σ >60 MPa).